Enhancing Arabic Writing Proficiency Through The Imlaʾ Manẓūr Method: A Case Study of Secondary School Learners in Indonesia - M. Ifdal; Idhan, Mohamad; Sidik, Jafar (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2025)
This study aims to determine how the application of the Imlā’ Manẓūr method improves the writing skills (maḥārah al-kitābah) of students in class X-A at MA DDI Ogoamas. Using a qualitative descriptive approach, data was collected through observation, interviews, and documentation and analyzed using data reduction, presentation, and verification techniques, accompanied by triangulation techniques for validity. The results indicate that the implementation of the Imlā’ Manẓūr method is effective in improving Arabic writing skills, as evidenced by improved understanding of the Arabic alphabet and the ability to connect letters. Educators also applied the al-ḥiwār technique through paired learning, supported by tools such as lesson plans, textbooks, laptops, and Android devices.